The place of German Grammar by Prof. Konstantin Galabov in university literature - Burova, Lilia (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The article examines the first academic German grammar (1950) in Bulgaria, written by the founder of the Department of German Studies at Sofia University Prof. Konstantin Galabov. Information is given both about the conditions under which the grammar was created and about some basic German grammars published in Bulgaria in the period between 1868 and 1944.